(untitled) (Baghdad Science Journal, 2023)
A set of ten drug compounds containing an amino group in the structure were determined theoretically. The parameters were entered into a model to forecast the optimal values of practical (log P) medicinal molecules. The drugs were evaluated theoretically using different types of calculations which are AM1, PM3, and Hartree Fock at the basis set (HF/STO-3G). The Physico-chemical data like (entropy, total energy, Gibbs Free Energy,…etc were computed and played an important role in the predictions of the practical lipophilicity values. Besides, Eigenvalues named HOMO and LUMO were determined. Linearity was shown when correlated between the experimental data with the evaluated physical properties. The statistical analysis was used to analyze the descriptors like multiple linear regression analysis performed to derive quantitative structure-activity relationship models which were further evaluated for the values of the prediction. The correlation coefficient gives an excellent relationship of more than (0.980, 0.980, and 0.978) for AM1, PM3, and HF/STO-3G respectively. A docking study was applied for the interaction of medicines with protein. All the drugs were connected with the protein to give the best energy stability for the docking mixtures. Nepafenac (compound No. 8) had the most stable energy with the protein compared with the 4-Aminosalicylic acid (compound No. 2) which had less energy stability.